2012
DOI: 10.1002/pen.23083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber modification with a novel compatibilizer on the mechanical properties and water absorption of hemp‐fiber‐reinforced unsaturated polyester composites

Abstract: Hemp‐fiber‐reinforced unsaturated polyester (UPE) composites were prepared by compression molding. The treatment of hemp fibers with N‐methylol acrylamide (NMA) and sulfuric acid as a catalyst significantly increased tensile strength, flexural modulus of rupture and flexural modulus of elasticity, and water resistance of the resulting hemp–UPE composites. Fourier transform infrared (FTIR) spectra revealed that some NMA was covalently bonded to hemp fibers. Scanning electronic microscopy graphs of the fractured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[21,[25][26][27][28][29][30][31][32]. Our previous researches indicated that the treatment of hemp/kenaf fibers by using some bifunctional monomers such as isocyanatoethyl methacrylate, 3-isopropenyldimethylbenzyl isocyanate, and N-methylol acrylamide significantly improved the interfacial adhesion between the hemp/kenaf fibers and UPE resins, leading to enhanced mechanical properties and water resistance of the resulting composites [33][34][35][36]. In this study, 1,6-diisocyanatohexane (DIH) and 2-hydroxyethyl acrylate (HEA) were adopted to treat bamboo fibers for improving the strength and water resistance of bamboo fibers-UPE composites.…”
Section: Introductionmentioning
confidence: 99%
“…[21,[25][26][27][28][29][30][31][32]. Our previous researches indicated that the treatment of hemp/kenaf fibers by using some bifunctional monomers such as isocyanatoethyl methacrylate, 3-isopropenyldimethylbenzyl isocyanate, and N-methylol acrylamide significantly improved the interfacial adhesion between the hemp/kenaf fibers and UPE resins, leading to enhanced mechanical properties and water resistance of the resulting composites [33][34][35][36]. In this study, 1,6-diisocyanatohexane (DIH) and 2-hydroxyethyl acrylate (HEA) were adopted to treat bamboo fibers for improving the strength and water resistance of bamboo fibers-UPE composites.…”
Section: Introductionmentioning
confidence: 99%
“…SNC and AM-SNC clearly shared similar spectral properties at wavelengths of 1450 and 1370 cm –1 (C–H bending vibration), 1648 cm –1 (H–O–H bending vibration), 1157 cm –1 (C–O stretching vibration), and 1155, 1080, and 1020 cm –1 (C–O–O stretching vibration). However, the AM-SNC spectrum exhibited new peaks at 1491 and 1577 cm –1 , indicative of an amino group and N–H bending vibration, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the stiffness of PP increased by 67% when PP was reinforced with MPS treated hemp fibres, and by only 30% when PP was reinforced with untreated hemp fibres (Panaitescu et al 2016). 158.6%, respectively, when compared with untreated hemp fibre reinforced composites (Qiu et al 2012).…”
Section: Graft Co-polymerizationmentioning
confidence: 98%
“…7.8 GPa were obtained in composites made from 2% DIH combined with 1.4% HEA treated hemp fibres(Qiu et al 2011). Besides using DIH and HEA, grafting N-methylol acrylamide (NMA) onto fibre surfaces in the presence of sulfuric acid as a catalyst has been found to increase tensile strength, MOR and MOE of hemp fibre reinforced unsaturated polyester composites(Qiu et al 2012). Treatment of hemp fibres with 3% (w/w) of NMA increased the tensile strength, flexural strength and flexural modulus of composites by 42.0%, 92.9%, and…”
mentioning
confidence: 99%